Music between ontology and ideology (Cambridge Scholars Publishing, 2020)
This book focuses on two main topics related to the essence of music, the first of which problematizes the ontological unity of music, philosophy and mathematics. The second concern of the text is the direction of social ontology or the existence of music in the context of ideological debates about style. The book looks at music's role as part of social ontology, and the part it played in documentarily recreating the post-Stalinism of the late 1950s and 1960s.